EMPLOYEE ENGAGEMENT AS A STRATEGIC MECHANISM LINKING SAFETY CULTURE AND DIGITAL TRANSFORMATION TO SUSTAINABLE PERFORMANCE IN INDONESIAN COAL MINING - Joni Pratikno; Irsan Tricahyadinata; Saida Zainurossalamia ZA (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Purpose - This study examines how safety culture and digital transformation shape employee engagement and sustainable performance in a high-risk coal mining context. It also investigates whether employee engagement mediates the effects of safety culture and digital transformation on sustainable performance. Design/methodology/approach - A quantitative explanatory design was used. Survey data were collected from 204 employees of PT Indominco Mandiri Bontang, Indonesia, selected from a population of 422 employees using proportionate stratified random sampling. The research model was tested with partial least squares structural equation modelling (PLS-SEM) using SmartPLS 4.0. The measurement model was assessed through outer loadings, Cronbach's alpha, composite reliability, average variance extracted, and Fornell-Larcker discriminant validity. The structural model was evaluated through R-square, f-square, path coefficients, and bootstrapped indirect effects. Findings - Safety culture has significant positive effects on employee engagement and sustainable performance. Digital transformation also has significant positive effects on employee engagement and sustainable performance. Employee engagement significantly improves sustainable performance and partially mediates both the safety culture-sustainable performance and digital transformation-sustainable performance relationships. The model explains 53.1% of the variance in employee engagement and 65.0% of the variance in sustainable performance. Originality/value - The study contributes to human resource management, safety management, and digital transformation literature by showing that sustainable performance in mining is not generated solely by safety systems or digital technologies, but by the ability of organizations to convert those resources into employee engagement. The findings extend the job demands-resources, social exchange, and resource-based perspectives to an under-researched Indonesian coal mining setting.